2018
DOI: 10.1111/1752-1688.12624
|View full text |Cite
|
Sign up to set email alerts
|

Floodplain Trapping and Cycling Compared to Streambank Erosion of Sediment and Nutrients in an Agricultural Watershed

Abstract: Floodplains and streambanks can positively and negatively influence downstream water quality through interacting geomorphic and biogeochemical processes. Few studies have measured those processes in agricultural watersheds. We measured inputs (floodplain sedimentation and dissolved inorganic loading), cycling (floodplain soil nitrogen [N] and phosphorus [P] mineralization), and losses (bank erosion) of sediment, N, and P longitudinally in stream reaches of Smith Creek, an agricultural watershed in the Valley a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 73 publications
(189 reference statements)
0
3
3
Order By: Relevance
“…Gillespie et al (2018) for Smith Creek, VA estimated floodplain deposition ranging from 0.7 to 1.7 cm/year (average: 1.1 cm/year), higher than the 0.26 cm/year median value measured here. This is noted in their study as remarkably high, especially when compared to other noteworthy sediment budget studies for agricultural watersheds both within and outside of the Chesapeake Bay watershed.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Gillespie et al (2018) for Smith Creek, VA estimated floodplain deposition ranging from 0.7 to 1.7 cm/year (average: 1.1 cm/year), higher than the 0.26 cm/year median value measured here. This is noted in their study as remarkably high, especially when compared to other noteworthy sediment budget studies for agricultural watersheds both within and outside of the Chesapeake Bay watershed.…”
Section: Discussioncontrasting
confidence: 62%
“…Counties, PA (rates of 5.0 to >20 cm/year) (Walter & Merritts, 2008). Gillespie et al (2018) for Smith Creek, VA estimated floodplain deposition ranging from 0.7 to 1.7 cm/year (average: 1.1 cm/year), higher than the 0.26 cm/year median value measured here. This is noted in their study as remarkably high, especially when compared to approach is recommended by Crema and Cavalli (2018), however this contrasts with the approach originally used by Borselli et al (2008) and this study.…”
Section: Comparison To Other Sediment Budget Studiescontrasting
confidence: 59%
“…Stream reaches switched from being typically erosional in first through third‐order streams, neutral in fourth‐order, and depositional in fifth and sixth order streams of the Difficult Run watershed (Hopkins et al, 2018; Hupp et al, 2013). In contrast, Gillespie et al (2018) found that sediment balance was depositional among sites in third‐ or fourth‐order streams, but decreasingly so in larger streams, of an agricultural Virginia watershed. Pizzuto et al (2018) measured that floodplain deposition was more than three times greater than bank erosion along a fifth‐order stream.…”
Section: Sediment Sources Transport and Deliverymentioning
confidence: 89%
“…Floodplain deposition Floodplains can trap sediment through both deposition of channel load during overbank flooding as well as by riparian buffering of sediments eroded from adjacent uplands. Floodplain deposition is spatially variable through the watershed depending on land use, geology, reach geomorphology, and floodplain hydrologic connectivity (Gellis et al, 2009;Gillespie et al, 2018;Hopkins et al, 2018;Hupp et al, 2013;Noe & Hupp, 2005;Pizzuto, Skalak, Pearson, & Benthem, 2016;Schenk, Hupp, Gellis, & Noe, 2013;Wolf, Noe, & Ahn, 2013). In general, greater rates of floodplain sedimentation occur where greater sediment load is transported by streams, greater hydrologic connectivity exists between stream channels and floodplains, and floodplain complexity is greater (like highly variable microtopography, coarse woody debris, and plant biomass).…”
Section: Box 4 Management Implication: Gulliesmentioning
confidence: 99%
See 1 more Smart Citation